Firms' expectations on access to finance at the early stages of the Covid-19 pandemic - Annalisa Ferrando; Ioannis Ganoulis (European Central Bank (ECB), 2020)
This paper provides novel information on the propagation of the pandemic-induced real shock to firms' financial conditions. It uses firm-level survey data from end February to early April 2020 for a large sample of euro area SMEs and large firms. Firms' expectations on the availability of credit lines, bank loans and trade credit deteriorated significantly in the first half of March. Firms mostly expected to be affected if they had previously difficulties in securing finance, had higher indebtedness and, hence, less capacity to deal with a liquidity shock. Conditional on these factors, firm size does not seem to matter, except for trade credit, in which case SMEs had more positive conditional expectations. Together with the overall deterioration of expectations, there seems to have also been a reallocation of opportunities to access finance amidst the crisis. Small firms were more likely to have conditional expectations of improvement in their access to finance.
Keywords: C83; D22; D84; E65; L25; 330; COVID-19; expectation formation; survey data